2019
DOI: 10.1007/s11218-019-09488-4
|View full text |Cite
|
Sign up to set email alerts
|

Alumni loyalty drivers in higher education

Abstract: Alumni can be of enormous value for higher education institutions because of the time and money they can spend on their former institution. Going beyond prior research that has as yet mostly considered alumni giving, this study focuses on exploring drivers for non-monetary alumni behavior (i.e., alumni loyalty). Modeling analysis was conducted on 152 alumni responses from two Dutch universities of applied sciences. Based on social exchange theory, a structural equation model was tested in which relationship qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 47 publications
5
36
0
2
Order By: Relevance
“…The literature usually presents overall quality as a relevant atribute influencing behavioral intentions (e.g. Alves & Raposo, 2007;Baade & Sundberg, 1996;Hennig-Thurau et al, 2001;Snijders et al, 2019), but there is a slight parallel between our results and those of Jiewanto et al (2012), who found that service quality had a negative impact on word-of-mouth intention, as well as with the conclusions of Rojas-Méndez et al (2009), who assert that service quality does not directly influence student loyalty. We think that an explanation for that may be the alumni's intention to contribute to overall success of the HEI, namely helping to improve services quality.…”
Section: Analysing the Binary Logistic Regression Modelsupporting
confidence: 76%
See 2 more Smart Citations
“…The literature usually presents overall quality as a relevant atribute influencing behavioral intentions (e.g. Alves & Raposo, 2007;Baade & Sundberg, 1996;Hennig-Thurau et al, 2001;Snijders et al, 2019), but there is a slight parallel between our results and those of Jiewanto et al (2012), who found that service quality had a negative impact on word-of-mouth intention, as well as with the conclusions of Rojas-Méndez et al (2009), who assert that service quality does not directly influence student loyalty. We think that an explanation for that may be the alumni's intention to contribute to overall success of the HEI, namely helping to improve services quality.…”
Section: Analysing the Binary Logistic Regression Modelsupporting
confidence: 76%
“…Positive feelings expressed in "pride in having been a student of the HEI" and "perception of the HEI as a trusted institution", demonstrate strong reasons to maintain the relationships with HEI in line with the related literature (e.g. Adidam, et al, 2004;Hennig-Thurau et al, 2001;Holdford & White, 1997;Snijders et al, 2019;Wong & Wong, 2011).…”
Section: Summary Of Findingssupporting
confidence: 69%
See 1 more Smart Citation
“…The relationship quality construct includes five relationship quality dimensions (Roberts et al, 2003). Based on the relationship quality research by Snijders andcolleagues (2018, 2019)), Roberts et al (2003) applied these dimensions in the context of higher education where they represent: students' trust in educational faculty/staff's honesty, students' trust in educational faculty/staff's benevolence, students' affective conflict, students' affective commitment, and students' overall satisfaction related to their educational faculty/staff's performance (Snijders et al, 2018(Snijders et al, , 2019.…”
Section: Student-faculty Relationship Qualitymentioning
confidence: 99%
“…For example, in business-to-business relations, consumers or customers are called buyers, while in commercial services such as life insurance, customers are called clients, and in health care, they are called patients. While rarely applied to institutions of higher education (Ng & Forbes, 2009), measurement of relationship quality as defined in consumer services is also applicable to the higher education context (Snijders, Rikers, Wijnia, & Loyens, 2018;Snijders, Wijnia, Rikers, & Loyens, 2019;Bowden, 2011;Hennig-Thurau et al, 2001). Although the 'student as consumer' approach is still debated in the literature (see, Bunce, Baird, & Jones, 2017;Tomlinson, 2017), students can be seen as the main recipients of educational services (Braun & Zolfagharian, 2016).…”
mentioning
confidence: 99%